FINANCIAL PROBLEMS OF POLISH CREDIT UNION SECTOR - Jacek Binda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
For several years now, there has been more and more information on the difficulties of the co-operative credit union sector in Poland. The Financial Supervision Authority in its reports has pointed to poor financial performance of the sector, intricate capital and personal links between the companies operating within the SKOK Holding S.a.r.l. and, finally, a growing number of credit unions being subject to recovery proceedings1. This paper attempts to present the credit union sector in Poland and its current financial situation. The conclusions of the paper confirm that the condition of the credit union sector is weak and that corrective actions such as recapitalization of the sector, its acquisition by the banking sector or other financial institutions as well as the creation of the so-called “bad bank” are absolutely necessary.